(untitled) (Research, Society and Development, 2020)
The objective of this work was to estimate the genetic parameters and correlations in common bean lines and cultivars, besides characterizing these genotypes by their agronomic components through principal component analysis. The assay was conducted at the State University of Mato Grosso do Sul, with 22 common bean genotypes in a randomized block design with three replications. With the use of seven agronomic characters related to productivity. The genotypes showed wide variability for virtually all evaluated characters, and the phenotypic variation observed occurred as a function of genotypic variance. When treatments are fixed, heritability is called genotypic determination coefficient (R2), this parameter ranged from 53.24% to 84.51%. The characters MCG and ALP showed promise for selection, since they presented the highest Values of R2, and also presented the quotient b higher than the unit. High significant genotypic correlations were found among ALPxAIV (0.63). The results of the principal component analysis (PCA) indicate the strong relationship between agronomic variables and genotypes. In the PCA, the lines CNFC 16548, CNFC 16566 and CNFC 16484 stood out for PROD, NVP and NR.